Pearls of the Czech New Wave - Menzel, Jiří 1938-2020; Němec, Jan 1936-2016; Schorm, Evald 1931-1988; Chytilová, Věra 1929-2014; Jires, Jaromil 1935-2001; Hrabal, Bohumil 1914-1997 (The Criterion Collection, 2012)
"Set against the backdrop of a repressed Czechoslovakia, five non-related vignettes are presented, each showcasing the need and want for human connection. [...]" [imdb.com]
Original: CS 1966
Epidodenfilm. - 5 Kurzfilme
Keywords: Film; DVD-Video